2017
DOI: 10.1093/fampra/cmx013
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of the 10-step patient engagement framework for patient-centred outcomes research studies: the first three steps

Abstract: Researchers' views illustrate the need to re-evaluate patient engagement in PCOR based on current realities. Given the many challenges to engagement that researchers encounter, it may be more productive to redefine the process of patient engagement so that the issues researchers now face are taken into account in future funding announcements, engagement rubrics and methodology frameworks developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Our experiences echo those of Sofolahan-Oladeinde et al, who describe positive experiences and local challenges at the start of their foray into patient engagement activities. 17 We found family engagement in deceased organ donation research faces similar challenges, such as limited time and resources, 5,12,17 as those reported in other research contexts. We also identified a new challenge posed by grief of family members with experience of deceased organ donation.…”
Section: Discussionsupporting
confidence: 56%
“…Our experiences echo those of Sofolahan-Oladeinde et al, who describe positive experiences and local challenges at the start of their foray into patient engagement activities. 17 We found family engagement in deceased organ donation research faces similar challenges, such as limited time and resources, 5,12,17 as those reported in other research contexts. We also identified a new challenge posed by grief of family members with experience of deceased organ donation.…”
Section: Discussionsupporting
confidence: 56%
“…We clustered the benefits into three domains: usability benefits, societal benefits and funding benefits. Usability benefits refer to impact on the topic generation and prioritization process, for example more relevant topics and priorities based on patients’ needs and the relevance of studies, for example more relevant research questions and medical interventions or technologies . Societal benefits refer to the way public and private resources are allocated, for example more appropriate resource allocation based on patients’ needs .…”
Section: Resultsmentioning
confidence: 99%
“…A number of articles identified in this review note the importance of acknowledging and addressing the diversity of patient stakeholders who are engaged as partners in research, a well‐established challenge . Addressing diversity through efforts that are now emerging to help overcome the challenges can better ensure a range of voices are captured that will enhance the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%